Analyse des éléments de gamification dans les applications d’apprentissage des langues : exploration des préférences et des pratiques des utilisateurs - Jaworska, Anna; Wesołowska, Karolina (Neofilolog, 2025)
Elements of gamification are increasingly being integrated into educational contexts, including language learning applications. While studies highlight benefits such as enhanced motivation and improved learning outcomes, few focus on the specific gamification features that make language learning apps appealing to users. This study analyzes the use of gamification elements in language learning apps and investigates user preferences. The study was divided into two phases. Its first part, a literature review, identified that points, leaderboards, levels, challenges, rewards, and content personalization are the most commonly used gamification features. Duolingo emerged as the most gamified app. The second phase of the study involved a quantitative analysis of survey data collected from 80 university students. Respondents were grouped into daily and occasional users of Duolingo. Data were gathered through a Google Forms survey distributed via student Facebook groups. The responses were analyzed statistically to examine correlations between preferences for gamification elements and motivations for language learning. The results showed that external motivations correlated positively with preferences for rewards and points, particularly among daily users. In contrast, users motivated by self-development preferred challenges. The analysis also revealed stronger correlations between gamification preferences and learning motivations in occasional users.